Redifferentiated Chondrocytes for the Repair of Articular Cartilage Lesions. Issue 7 (21st July 2017) - Bianchi, Vanessa Juliana; Theodoropoulos, John S.; Kandel, Rita; Backstein, David
Objectives: Biological therapies such as autologous chondrocyte implantation which use serially passaged chondrocytes to repair cartilage defects, are often unsuccessful as they lead to the formation of fibrocartilage. Fibrocartilage is rich in collagen type 1 (Col1) and lacks the structural complexity, low friction, and load distribution properties of articular cartilage. Fibrocartilage forms as a result of the phenotype of passaged chondrocytes. When serially passaged in monolayer to increase cell numbers, chondrocytes lose their phenotype in a process termed "dedifferentiation". This is characterized by a loss in the production of collagen type II (Col2) and aggrecan (Acan), the major extracellular matrix molecules of articular cartilage, and an increase in the production of Col1. Therefore, to increase the success of therapies which use passaged chondrocytes, these cells must be redifferentiated to re-establish an articular cartilage phenotype prior to implantation in a cartilage lesion. Transforming growth factor beta (TGFβ) signalling is known to play important roles in both cell differentiation and articular cartilage repair. However, intra-articular injections with TGFβ have been shown to result in osteophyte formation and fibrosis of synovial tissues. Therefore, redifferentiating passaged chondrocytes in vitro using TGFβ prior to their use in vivo may be a better alternative. Fibrin glue is commonly used in orthopaedics to maintain cells in a cartilage lesion, however the effects of fibrin glue on chondrocytes have not been fully investigated. Thus we hypothesize that passaged chondrocytes redifferentiated in vitro with TGFβ will maintain their phenotype and form articular cartilage-like tissue when embedded in fibrin glue in the absence of further exogenous supplementation with TGFβ in vitro. Methods: Chondrocytes were enzymatically isolated from rabbit articular cartilage and serially passaged in monolayer twice (P2) to increase cell number and facilitate dedifferentiation. P2 cells were cultured in scaffold-free 3D using a chondrogenic serum-free media supplemented with 10ng/ml TGFβ3 to facilitate redifferentiation. Redifferentiated chondrocytes were then embedded in fibrin glue (Tisseel, Baxter) at 1.5 x 10 6 cells/20uL and cultured for 2 weeks in vitro in the absence of TGFβ3. Controls were P2 cells that were not redifferentiated with TGFB3 prior to embedding in fibrin glue. Histology and immunohistochemistry were used to assess tissue formation and cell phenotype. Results: Redifferentiated chondrocytes accumulated more matrix rich in Col2 and Acan than controls (Figure 1). Furthermore, redifferentiated chondrocytes had a round cell shape characteristic of articular chondrocytes. The use of fibrin glue did not impair the ability of redifferentiated chondrocytes to accumulate matrix nor did it affect cell phenotype. Conclusion: Redifferentiated chondrocytes in fibrin glue may be a better alternative to passaged chondrocytes for cell based articular cartilage repair therapies as they accumulate more Col2 and Acan containing matrix than undifferentiated P2. In vivo studies are required to elucidate the potential for redifferentiated chondrocytes in cartilage repair.